Pertimbangan Hukum terhadap Putusan Lepas dari Segala Tuntutan Hukum (Ontslag Van Rechtsvervolging) - Anak Agung Gede Wiweka Narendra; I Gusti Bagus Suryawan; I Made Minggu Widyantara (Warmadewa Press, 2020)
People’s knowledge and understanding of the community, especially law enforcement officials as the one who implement the laws and regulations, often causes mistakes in interpreting the criminal act of fraud. Evidence shows that the public or law enforcement officials who carry out their duties if a legal relationship is carried out by someone with another person, which was originally very civil in nature (individual contract), can often develop into a complex problem because it contains other juridical aspects, for example the dimension of the crime. This study aims to determine the judge's consideration in giving a decision that is free from all lawsuits as well as the legal remedies that can be made on a decision that is free from all lawsuits in criminal cases. This study uses a descriptive normative research method. Sources of data used are secondary legal materials as the basis for research. Data collection in this study was carried out by literature study (document study), namely the collection of legal materials through written legal materials with deduction analysis techniques. Deductive analysis is drawing conclusions from general matters regarding the concrete problems faced. After the analyzing the data, the results showed that the basis for the judge's consideration of giving a verdict that is free from all lawsuits is if the accused can be proven legally and convincingly and strengthened by evidence so that the judge's conviction is obtained but it is not included in a criminal act as contained in Article 191 point (2) KUHAP which requires that it be declared to be released from all legal demands.